War and Revolution in South China : The Story of a Transnational Biracial Family, 1936-1951 - Rhoads, Edward J. M. (Royal Asiatic Society Hong Kong studies series., 2021)
In War and Revolution in South China, Edward Rhoads recounts his childhood and early teenage years during the Sino-Japanese War and the early postwar years. Rhoads came from a biracial family. His father was an American professor while his Chinese mother was a typist and stenographer. In the late 1930s and the 1940s, the Rhoads family lived through the turbulent years in southern China and Hong Kong. The book follows Rhoads' childhood in Guangzhou, his family's evacuation to Hong Kong, his father's internment and repatriation to the United States, and his and his mother's flight to Free China. He recalls his reunion with family members in northern Guangdong Province in 1943, their retreat to China's wartime capital of Chongqing, where his father worked for the American government, and how they returned to Guangzhou after the war. The Rhoads family then witnessed the socioeconomic recovery in the city and the regime change in 1949. The book ends with their departure from China to the United States in 1951, a year and a half after the Communist revolution. The book fills an important gap in the scholarship by examining the impact of the Sino-Japanese War in southern China from the perspective of one family. Rhoads reveals that the war in this region, while often neglected by scholars, was in fact no less turbulent than it was in northern and central China. He combines autobiography with serious historical research to reconstruct the lives of his family, consulting a large number of archival documents, private correspondence, and scholarly literature to produce a rare study that is both scholarly and accessible.